CERTIFICATE OF ACCREDITATION BACHELOR OF SOCIAL SCIENCES WITH HONOURS (INTERNATIONAL RELATIONS) (MQA/FA10753) (2018) - Jasmine, Jugah
MALAYSIAN QUALIFICATION AGENCY- CERTIFICATE OF ACCREDITATION BACHELOR OF SOCIAL SCIENCES WITH HONOURS (INTERNATIONAL RELATIONS) (MQA/FA10753) (2018), FACULTY OF SOCIAL SCIENCES AND HUMANITIES